Electronic Building Permission System: The Case of Greece. (2015) - Bellos, Christos V.; Petroutsatou, Kleopatra; Anthopoulos, Leonidas
Abstract: Electronic building permission systems have been used in several European countries from the early 70s (i.e. Italy, France and Netherlands), while in USA are being utilized several components and sub-modules of the system from the early 30s. The European Commission defined the electronic application for Building Permission as one of the 20 primary e-Government services, which each European Member State was obliged to deliver online by 2005, according to the e-Europe strategies (e-Europe2003). However, Greece, as well as several other European countries failed to address this challenge and the goal of an electronic building permission system across Europe was extended, initially until 2010 (i2010 strategy) and eventually until 2020 (Horizon 2020 strategy). The current study initially defines the primary and secondary functionalities that such a system should have. Furthermore, the study examines the factors that influence the success or failure of such a project and proceed to a case study investigation in Greece by examining the current situation and the level of absorption of the European i2010 strategy regarding the electronic building permission. The research framework encompasses a literature survey of publications and official reports in order to shape a "clear picture" regarding the different approach of e-service delivery. In addition, in this paper are analyzed the results of structured questionnaires that have been sent and of interviews that have been conducted with public organizations in Greece that are responsible for the implementation, installation and utilization of such a system (i.e. Information Society in Greece, Municipalities). In conclusion, this research investigates the framework of the building permission e-services and its current situation in Greece that leads to: (a) an effective public management administration by simplification of licensing procedures, (b) a reduction of depraved behavior and (c) environmental benefits by reducing bureaucracy.